2008
DOI: 10.1021/jf800575p
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Supplementation with Cysteamine on Growth Hormone Receptor and Insulin-Like Growth Factor System in Finishing Pigs

Abstract: The present study was conducted to test the hypothesis that chronic cysteamine (CS) supplementation may affect serum insulin-like growth factor (IGF)-I concentrations and growth hormone (GH) receptor (GHR), IGF-I, IGF-I receptor (IGF-IR), IGF binding protein (IGFBP)-3, and insulin receptor (IR) mRNA levels in different tissues of finishing pigs. A total of 24 finishing pigs (60.05 +/- 1.24 kg; 12 gilts and 12 barrows) were assigned randomly to one of the three dietary groups, with four pens/group (per pen: one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 21 publications
(33 reference statements)
8
14
0
Order By: Relevance
“…IGF-1 increased amino acid transport [18] and protein synthesis [19] in the cultured cells in vitro. IGF-I can also stimulate amino acid uptake and protein synthesis in muscles and can greatly reduce the rate of protein breakdown within muscle fibers [20]. In the present study, insulin increased the mRNA levels of IGF-1, and this effect could be enhanced by the addition of different forms of chromium: CrSP is the highest, followed by CrPic, then CrCl 3 .…”
Section: Discussionsupporting
confidence: 54%
“…IGF-1 increased amino acid transport [18] and protein synthesis [19] in the cultured cells in vitro. IGF-I can also stimulate amino acid uptake and protein synthesis in muscles and can greatly reduce the rate of protein breakdown within muscle fibers [20]. In the present study, insulin increased the mRNA levels of IGF-1, and this effect could be enhanced by the addition of different forms of chromium: CrSP is the highest, followed by CrPic, then CrCl 3 .…”
Section: Discussionsupporting
confidence: 54%
“…28 Our data highlighted that LOC781250 upregulation might be due to increased GSH content in oocytes, which acts as a reservoir to protect zygotes and promotes embryonic development. Our data support the results of the study by Guangmang et al 29 who established that IGF-I mRNA levels were upregulated after dietary supplementation with cysteamine on growth hormone receptor and insulin-like growth factor in finishing pigs. 29 It also increases the proportion of preimplantation embryos developing into blastocysts, alters blastocyst gene expression, and improves embryo resistance to various stresses.…”
Section: Discussionsupporting
confidence: 92%
“…In many studies, the positive correlation between cysteamine and growth performance and FE has been found in fishes, rats, pigs, and broilers . In our study, no significant difference was found in feed conversion ratio, thus corroborating the study by Liu et al ., who also found no significant difference in FE between treatments with 0.070 g kg −1 cysteamine and control in finishing pigs. These results indicate that increasing the feed conversion ratio by at least 8% through dietary CC might improve economic returns in swine industry.…”
Section: Discussionsupporting
confidence: 91%